-10=6-4r

Simple and best practice solution for -10=6-4r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10=6-4r equation:


Simplifying
-10 = 6 + -4r

Solving
-10 = 6 + -4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '4r' to each side of the equation.
-10 + 4r = 6 + -4r + 4r

Combine like terms: -4r + 4r = 0
-10 + 4r = 6 + 0
-10 + 4r = 6

Add '10' to each side of the equation.
-10 + 10 + 4r = 6 + 10

Combine like terms: -10 + 10 = 0
0 + 4r = 6 + 10
4r = 6 + 10

Combine like terms: 6 + 10 = 16
4r = 16

Divide each side by '4'.
r = 4

Simplifying
r = 4

See similar equations:

| -5=7+(n-1)-1 | | -5=7+(n-1)3 | | -5=3+(n-1)7 | | -5=3+(n-1)-1 | | x=5t^2+2t+5 | | 3=-1+(n-1)7 | | 3=-1+(n-1)-5 | | 3=7+(n-1)-5 | | 3=-5+(n-1)7 | | 3=-5+(n-1)-1 | | 3=7+(n-1)-1 | | 7=-1+(n-1)3 | | -1(6)=-5+(n-1)3 | | -1(6)=7+(n-1)3 | | -5(6)=-1+(n-1)3 | | -3+2=2x-8 | | h=-15t^2+90t | | x^3-17x^2+82x-120=0 | | 8-3(5x+9)-10=16 | | F(5)=-3x^2+8 | | N+6=-9 | | F(x)=-3x^2+8 | | F(x)=-3x^8 | | x(x+5)=-9 | | (-2x^3y^2)(0)(-3x^4y)= | | (x+3)2=14 | | 1/6-u-1/4-u=0 | | 1/6-u-1/4-4=0 | | 2y/13-13y/2=-15 | | f(x)=x^2-6x+14 | | 2y/13-13y=-15 | | 7x-42=66-9x |

Equations solver categories